A Study to Evaluate the Effectiveness of Sensory Stimulation Program (SSP) on Motor Function (MF) and Verbal Response (VR) Among Patients with Stroke in ICU of Selected Hospitals at Salem - Guna Priya. G; Shenbagavalli. E (International Journal of Emergency and Trauma Nursing and Practices, 2024)
Introduction: Stroke is a medical emergency and can cause permanent neurological damage, complications and death. Objectives: (1)To develop and validate a Sensory Stimulation Program aimed at enhancing motor function (M.F) and vital signs recovery (V.R) in stroke patients. (2)To evaluate and compare the pre-test and post-test scores of M.F and V.R in stroke patients receiving routine nursing care. (3)To assess and compare the pre-test and post-test scores of M.F and V.R in stroke patients who undergo the Sensory Stimulation Program in addition to routine nursing care. (4) To explore the connection between the M.F. and V.R. of the experimental group and their demographic characteristics, such as age and identified stroke risk factors. Hypotheses: H1: Patients with stroke who undergo the Sensory Stimulation program are expected to have significantly higher scores in motor function (M.F) and vital signs recovery (V.R) compared to those who receive only routine nursing care.H2: A notable correlation is anticipated between the post-test scores for motor function (M.F) and vital signs recovery (V.R) in the experimental group and their chosen demographic variables. (Age, selected risk factors for stroke) Methods: This was quantitative quasi-experimental pre-test post-test design study. The Samples were the stroke patients undergoing treatment in Selected Hospital in Salem with mild Motor function and verbal response. The sampling technique employed was a non-random convenience sampling method. Demographic data was collected to capture the characteristics of the sample. It included age, gender, marital status, Role of an individual, Risk factors associated with stroke. A rating scale was used to evaluate motor function and verbal response in the samples, based on the Glasgow Coma Scale (GCS) scoring system. The score was categorized and it consists of 3 components such as eye opening, verbal response, motor response. Results: The study findings indicate that, in the pre-test assessment, 87% of patients exhibited poor motor function and verbal response, while 13% showed moderate motor function and verbal response. In the post-test results, 60% of participants displayed good motor function and verbal response, 27% showed moderate motor function and verbal response, while 13% exhibited poor motor function and verbal response. The mean pre-test motor function and verbal response score was 5.4. The mean post-test motor function and verbal response score was 8.3. The mean paired ‘t’ test value was significantly higher than the table value (t14=14.32 > table value =2.145) at p table value = 2.78) at the p
Keywords: Stroke; evaluate; motor function; sensory stimulation program; verbal function